Key Performance Indicators (KPIs), Shipping Marketing and Safety Orientation: The Case of Greek Tanker Shipping Companies - Plomaritou, Evi; Konsta, Katerina (SPOUDAI Journal of Economics and Business, 2013)
If you are not sure where you are, how will you find out where to go? The aim of this paper is to examine the relationship between the KPIs and the shipping marketing as well as the usefulness of KPIs in shipping companies performance evaluation. The paper brings the importance of KPIs closer to the reader and examines their definition, purpose and role in the shipping company. The first part is devoted to literature review on KPIs. The second part examines the relationship among the KPIs, the shipping marketing and the safety orientation of tanker shipping companies. The third part includes the research methodology; since the tanker market is a safety oriented market, a questionnaire is taken across the tanker shipping companies in Greece. The third part is the analysis of the questionnaire which showed that KPIs improve the marketing planning, the customer relationships and the company’s competitiveness. The most important KPIs are safety, operational, technical, environmental, navigational, security and financial indicators. The final part is the conclusion. JEL Classification: M310; M100; M140; R410.